Radioactively driven colloids: A special case of anomalous diffusion - Wilson, Graham; Bahadori, Amir A.; Bindra, Hitesh (My University, 2018)
A novel concept of self-propelled, radioactively driven colloids is introduced. The focus of this paper is on assessing the impact of alpha emissions on colloidal kinematics. Using Langevin dynamics and a random walk model, a theory has been developed to describe this motion. This theory shows a special case of anomalous diffusion. Numerical simulations have substantiated the theory. It is shown that alpha-particle emission can significantly affect the motion of colloidal particles, although a very short-lived radioisotope is required.
Citation: Wilson, G., Bahadori, A. A., & Bindra, H. (2019). Radioactively driven colloids: A special case of anomalous diffusion. Journal of Applied Physics, 126(12), 124308. https://doi.org/10.1063/1.5116220